Teaching in IP Schools: An Analysis of Teachers' Experiences as Input to Pre-Service Teacher Education - Reyteran, Riza (International Journal of Language and Literary Studies, 2021)
The demand to make education inclusive requires assurance that the future teachers of indigenous students are fully equipped to handle multicultural classes. Hence, with an end goal of identifying inputs that could enhance pre-service teacher education, this study was conducted to determine the profile, experiences, knowledge, attitudes, and skills of the randomly selected teachers of indigenous students in the province of Occidental Mindoro. The data were gathered online through a questionnaire that underwent validity and reliability tests. Findings reveal that the teachers are graduates of bachelor of Elementary Education and have been teaching in the IP schools for not more than three years. The teachers frequently experience implementing the curriculum, monitoring student’s progress, and living with the IP community, and occasionally experience travelling to and from the IP community as they embark on the day-to-day activities of teaching their IP students. The knowledge, attitudes, and skills they have acquired from their pre-service teacher education curriculum have prepared them in teaching IP students. Five themes emanate from the teachers’ suggestions on how to enhance the pre-service teacher education curriculum such as inclusion of IP education, awareness program on the culture of Indigenous People, inclusion of IP language, training on how to handle combined or multigrade class, and conducting immersion activities in IP or minority schools. The College of Teacher Education may consider the suggestions of the teachers in reviewing and revising the existing curriculum of pre-service teacher education.